2013
DOI: 10.2458/azu_js_rc.55.16314
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of 14C Analysis of Carbonaceous Aerosols: Exercise 2009

Abstract: ABSTRACT. Radiocarbon analysis of the carbonaceous aerosol allows an apportionment of fossil and non-fossil sources of airborne particulate matter (PM). A chemical separation of total carbon (TC) into its subfractions organic carbon (OC) and elemental carbon (EC) refines this powerful technique, as OC and EC originate from different sources and undergo different processes in the atmosphere. Although 14 C analysis of TC, EC, and OC has recently gained increasing attention, interlaboratory quality assurance meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…The results presented in Figure 6 did not show a clear connection between the WIOC concentration of the filters or the EC recovery and the fraction modern of EC, but already a small amount of remaining OC can increase F 14 C(EC) significantly. [27], show a standard deviation for the uncorrected F 14 C(EC) data of 0.065 (Milan) and 0.117 (Ispra) for two ambient filter samples. F 14 C(EC) of ambient aerosol particle samples have been reported by previous studies [11,12,14,43] across Europe in a range from 0.1, mostly for filter samples from cities, to up to 0.8, measured during winter-time smog episodes related to wood burning in Switzerland [44].…”
Section: Analysis Of Radiocarbon In Ec: Results Of An Inter-comparisomentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented in Figure 6 did not show a clear connection between the WIOC concentration of the filters or the EC recovery and the fraction modern of EC, but already a small amount of remaining OC can increase F 14 C(EC) significantly. [27], show a standard deviation for the uncorrected F 14 C(EC) data of 0.065 (Milan) and 0.117 (Ispra) for two ambient filter samples. F 14 C(EC) of ambient aerosol particle samples have been reported by previous studies [11,12,14,43] across Europe in a range from 0.1, mostly for filter samples from cities, to up to 0.8, measured during winter-time smog episodes related to wood burning in Switzerland [44].…”
Section: Analysis Of Radiocarbon In Ec: Results Of An Inter-comparisomentioning
confidence: 99%
“…The most recent and comprehensive inter-comparison exercise of 14 C in carbonaceous aerosols [27] found that results of 14 C measurements in OC and TC generally agree well between the different laboratories, but results for EC showed large differences ranging from 28-79%. These values represent the inter-laboratory standard deviation of 14 C in EC for three different samples.…”
Section: Introductionmentioning
confidence: 99%
“…A recent community inter-comparison of 14 C measurements on aerosol samples demonstrated comparable results for aerosol total carbon (Szidat et al 2013). There is a need for future such comparisons of different techniques and operational definitions for isolating the EC fraction for 14 C measurements.…”
Section: Carbon Aerosol Mass Concentration and Isotope Analysesmentioning
confidence: 99%
“…Radiocarbon analysis ( 14 C) is a quantitative tool for unambiguously distinguishing fossil and nonfossil sources of EC and OC. 14 C is completely depleted in fossil fuel emissions ( 14 C half-life = 5730 years), which can therefore be separated from nonfossil carbon sources (e.g., biomass burning, cooking, or biogenic emissions) which have a similar amount of 14 C as atmospheric carbon dioxide (CO 2 ) [Szidat, 2009;Currie, 2000]. The 14 C measurement on the EC fraction is still challenging.…”
Section: Introductionmentioning
confidence: 99%